PENGARUH STRATEGI PEMBELAJARAN DAN KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR PADA MATERI SHALAT DI KELAS II (DUA) SDN RAMA 1 KOTA TANGERANG - Dian Astutik; Ety Kurniyati (Universitas Muhammadiyah Tangerang, 2021)
This study aims to find out the number of the influence of the learning strategy (X1), and pedagogical competence (X2) variables on the learning outcome variable (Y) of the prayer material at SDN Rama 1 Tangerang city, both partially and simultaneously. The method used in this study is a quantitative method, with respondents are all active students of Class II (two) of SDN Rama 1 in Tangerang City in the academic year of 2019/2020, which numbered 99 persons. The technique of analysis used are simple and multiple linear regression analysis, with the hypothesis test method are t test and f test. The results of the hypothesis tests state that partially or simultaneously the learning strategy (X1), and pedagogical competence (X2) variables have the positive and significant effects on the learning outcomes variable (Y), with the number of influence of each one partially that is 32.4%, and 76.4%. However, the number of the simultaneous influence of the two independent variables on learning outcomes is 46.4%, while the remaining 54.6% is influenced by other factors not examined in this study. Thus, if the learning strategy and teacher's pedagogical competence increase, the learning outcomes of the prayer material will also increase.